Pergulatan Hikmat dalam Kitab Pengkhotbah - V. Indra Sanjaya (Jurnal Orientasi Baru, 2010)
This writing intends to investigate the development of biblical wisdom tradition by comparing the Book of Qoheleth to the Book of Proverbs which was composed earlier. The comparison between those two textual traditions which is focused on two themes, namely, the reality and the human life, clearly indicates a significant development of ideas. Qoheleth argues that in real life, the Law of Retribution which is marshalled by traditional wisdom represented by Proverbs does not work. Nevertheless, Qoheleth has not arrived at a better solution yet. What it offers is just a carpe diem ideology as a preliminary solution to the problem.